MOR/SBA‐15 Composite Catalysts with Interconnected Meso/Micropores for Improved Activity and Stability in Isopropylation of Naphthalene. Issue 15 (19th June 2015) - Banu, Marimuthu; Lee, Young Hye; Magesh, Ganesan; Nam, Chang‐Mo; Lee, Jae Sung
Abstract The isopropylation of naphthalene with isopropyl alcohol was studied over composites of MOR/SBA‐15 in a high‐pressure, fixed‐bed reactor. The MOR catalyst showed a high 2, 6‐/2, 7‐diisopropyl naphthalene (DIPN) ratio of 1.75, but a low naphthalene conversion (54 %) and fast deactivation of the catalyst. The composites of MOR/SBA‐15 were prepared by a hydrothermal recrystallization process to obtain hierarchical micro/mesopores. During the process, MOR recrystallized in the mesopores of SBA‐15, the structure of which was stabilized by carbon coating formed on the pore walls as a template. The best prepared MOR/SBA‐15 catalyst achieved a high conversion of 85 %, high stability, and less coking, while maintaining the high 2, 6‐/2, 7‐DIPN ratio (≈1.8). The modified micro/mesopore structure allowed facile diffusion of bulky molecules to and from active catalytic sites located in the small MOR pores as a result of the connection between the two types of pores in the MOR/SBA‐15 composite.